Chronic Obstructive Pulmonary Disease A Current Conspectus - Chung Ong, Kian (IntechOpen, 2021)
Chronic Obstructive Pulmonary Disease - A Current Conspectus provides an update on COPD related to the following topics: • merging of experience with technology in confronting COPD • air pollution and work-related exposures as major causes of COPD • heterogeneity of COPD caused by smoke from cigarettes and biomass fuel • disease-related contributors of health status in COPD • exercise training in the context of pulmonary rehabilitation • nutritional interventions in COPD • mechanical ventilation in COPD • use of patient-directed music listening during mechanical ventilation